Coordinate transformation based coefficients estimation algorithm for digital predistortion of RF power amplifiers - GHao HUAN; Hua QIAN; Sai-jie YAO; Xiu-mei YANG (Tongxin xuebao)
Based on the low-IF digital predistortion (DPD) architecture,a coordinate transformation based low-complex coefficients estimation algorithm is proposed to reduce the hardware implementation cost and numerical calculation complexity significantly.The proposed algorithm transforms the complex multiplication of the conventional DPD coefficients estimation method to amplitude multiplication and phase addition in polar coordinates.To complete the same calculation,times of multiplications and accumulations are reduced by 75% and 50%.The algorithm is derived from the general Volterra pass-band nonlinear model,and proves the equivalency of baseband predistortion and IF predistortion.The proposed low-IF architecture and the coefficients estimation algorithm are verified by the measurement results on a practical radio frequency power amplifier.